UTILIZATION OF GEOSPASIAL INFORMATION TO IMPROVE MAKING MAP SKILL IN GEOGRAPHY LEARNING - Dony Purnomo (Universitas Sebelas Maret (UNS), 2019)
The aim of this reseach are: (1) To describe the use of geospatial information in improving the skills of students in making maps, (2) To improve the skills of students in making maps. This class action research uses two cycles with research subjects in class XI IPS 4 at SMAN 1 Purwantoro academic year 2018/2019. The indicator of success in this study is the classical completeness of students above 70% and there is an increase in student learning outcomes. The results of this study are (1) Utilization of geospatial information in improving map-making skills through several stages, namely introduction, gathering geospatial information, making maps, presentations, closing. (2) Utilization of geospatial information on geographic subjects can improve students' skills in making maps. Improvement of student learning outcomes is reflected in the percentage of classical completeness in the first cycle of 57.69% and in the second cycle rose to 88.46%. While the average value in classical in the first cycle of 69.82 rose to 82.38 in cycle 2.